2022
DOI: 10.3748/wjg.v28.i3.275
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial cells and blood vessels are major targets for COVID-19-induced tissue injury and spreading to various organs

Abstract: The coronavirus disease 2019 (COVID-19) infected so far over 250 million people and caused the death of over 5 million worldwide. Aging, diabetes, and cardiovascular diseases, conditions with preexisting impaired endothelial functions predispose to COVID-19. While respiratory epithelium is the main route of virus entry, the endothelial cells (ECs) lining pulmonary blood vessels are also an integral part of lung injury in COVID-19 patients. COVID-19 not only affects the lungs and respiratory system but also gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 95 publications
2
17
0
1
Order By: Relevance
“…This study also demonstrated an increased number of endothelial cells containing ACE2-receptors, as well as significant changes in the endothelial morphology of the lungs in autopsied patients with Covid-19 infection (Ackermann et al 2020). Under certain pathological conditions of existing endothelial dysfunction, the ACE/Ang II axis is overactivated, leading to vasoconstriction, thrombogenesis, fibrosis, coagulopathy, and thrombophilia (Tarnawski and Ahluwalia 2022).…”
Section: Introductionsupporting
confidence: 52%
See 2 more Smart Citations
“…This study also demonstrated an increased number of endothelial cells containing ACE2-receptors, as well as significant changes in the endothelial morphology of the lungs in autopsied patients with Covid-19 infection (Ackermann et al 2020). Under certain pathological conditions of existing endothelial dysfunction, the ACE/Ang II axis is overactivated, leading to vasoconstriction, thrombogenesis, fibrosis, coagulopathy, and thrombophilia (Tarnawski and Ahluwalia 2022).…”
Section: Introductionsupporting
confidence: 52%
“…Endothelial cells and blood vessels are targets, but also a mechanism for the spread of the SARS-CoV-2 virus, and associated tissue changes, as well as for its dissemination to various organs in the patient's body. Therefore, prior endothelial dysfunction could make endothelial cells more sensitive to the action of the virus, leading to the more severe systemic course of Covid-19 (Tarnawski and Ahluwalia 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6) COVID-19 damages not only the lungs and respiratory system but also other organs, such as the GI tract, liver, pancreas, kidneys, heart, brain, and skin. Notably, blood vessels and endothelial cells (ECs), which are the conduits for virus dissemination to these organs, can be injured by the virus [ 67 ]. However, the biological effects of paxlovid and nirmatrelvir on blood vessels and ECs have not been investigated.…”
Section: Several Issues Of Concernmentioning
confidence: 99%
“…The innermost layer of blood vessels is comprised of endothelial cells (ECs) that are heterogeneous in nature [ 51 ]. ECs are critical for supplying oxygen and nutrients to cells and tissues, and are involved in coagulation and generation of vasoactive substances, hormones and growth factors [ 52 ]. There are three main lung ECs, pulmonary microvascular, pulmonary artery and pulmonary vein ECs [ 53 ].…”
Section: To Generate Vascularized Hpsc-derived Lung Organoidsmentioning
confidence: 99%